2018
DOI: 10.1002/jso.25109
|View full text |Cite
|
Sign up to set email alerts
|

Staged margin‐controlled excision (SMEX) for lentigo maligna melanoma in situ

Abstract: SMEX offers a reliable surgical excision method that ensures complete excision of LM in a cosmetically sensitive manner. The recurrence outcomes of SMEX are comparable, if not better, than those of alternative excision techniques in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…36,39,47,48,[56][57][58][59][60][61] The weighted mean ± SD (range) surgical margin necessary for negative histological margins was 7.7 ± 2.0 mm (6.6-13.2) (n = 568). 42,43,46,47,49,56,61,62 Lentigo maligna melanoma. A 10 mm surgical margin resulted in negative histological margins in 78% (40/51) following WLE or SE with partial margin assessment.…”
Section: Surgical Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,39,47,48,[56][57][58][59][60][61] The weighted mean ± SD (range) surgical margin necessary for negative histological margins was 7.7 ± 2.0 mm (6.6-13.2) (n = 568). 42,43,46,47,49,56,61,62 Lentigo maligna melanoma. A 10 mm surgical margin resulted in negative histological margins in 78% (40/51) following WLE or SE with partial margin assessment.…”
Section: Surgical Marginsmentioning
confidence: 99%
“…In the subgroup analysis, the weighted mean ± SD (range) stages needed for histological clearance in patients treated by SE was 1.7 ± 0.1 (1.4-2.1) (n = 728), 40,42,44,46,49,56,62,65,66 compared with 1.1 ± 0.03 (1.1-1.2) when HH-RCM (n = 103) was used prior to SE 58,67 (p < 0.0001). Negative histological margins were obtained after the first stage in 86% (89/103) using HH-RCM prior to SE, 58,67 compared with 50% (217/433) without HH-RCM 47,53,57,61,66,68 (p < 0.0001).…”
Section: Surgical Stagesmentioning
confidence: 99%
“…Larger lesion diameter was directly correlated with the clinical margin width needed for histologic clearance. In their own variant of this technique, a group from Alberta, Canada reported on their experience using staged margin-controlled excision (SMEX) for the treatment of LM in 24 patients, predominantly located on the face and anterior leg [ 40 ]. They found that a mean of 9 mm clinical margins was required for histologic clearance, in line with prior data.…”
Section: Resultsmentioning
confidence: 99%
“…However, given that the study did not differentiate between different tumor sites, its findings are subject to controversial debate, even in the US where Mohs surgery is commonly used [5]. Other studies used paraffin-embedded tissue and/or involved wide local excision or staged procedures [2,3,6].…”
Section: Statement Of the German Society Ofmentioning
confidence: 99%